Policy Innovations, Political Preferences, and Cartel Prosecutions - Vivek Ghosal; D. Daniel Sokol (Center for Economic Studies and ifo Institute (CESifo), 2015)
While price-fixing cartel prosecutions have received significant attention, the policy determinants and the political preferences that guide such antitrust prosecutions remain understudied. We empirically examine the intertemporal shifts in U.S. antitrust cartel prosecutions during the period 1969-2013. This period has seen substantive policy innovations with increasing penalties related to fines and jail terms. There appear to be four distinct cartel policy regimes: pre-1978, 1978-1992, 1993-2003, and 2004-2013. Our empirical estimates show significant variation in the number of cartels prosecuted and the penalties imposed across the policy regimes. The more recent regimes are characterized by far fewer cartels prosecuted, but with substantially higher penalties levied on firms and individuals. While effective deterrence is one explanation for these patterns, we are more inclined to conclude that US cartel enforcement has seen an underlying shift away from focusing on smaller cartels to larger and multinational firms. In terms of political effects, our results reveal no clear inter-political party effect on cartel prosecutions, but there appear to be interesting intra-political party effects. We find that particular Presidencies matter for cartel prosecutions, and variation across Presidential administrations led to marked shifts in the total number of cartels prosecuted. Overall, the shifts in the number of cartels prosecuted and penalties levied portray changing policy priorities and a search for the optimal enforcement design to curtail one of the clearest sources of welfare loss, collusion.
Keywords: K21; L41; L13; L11; 330; cartels; collusion; price-fixing; enforcement; prosecutions; antitrust; leniency; fines; jail terms; Antitrust Amendments Act; ACPERA; politics; business cylces